(untitled) (Innovative professional education, 2025)
Modern trends in the innovative development of the hospitality industry are catalysts for the search by vocational education institutions for effective ways to organize professional training, which requires the integration of the efforts of education representatives and employers around the creation and implementation of such pedagogical conditions in the educational institution that would contribute to the formation of professional competence of education seekers and the development of «soft skills» in them. The results of the analysis of scientific works on the studied issues made it possible to determine and substantiate such pedagogical conditions for the development of «soft skills» in future restaurant service masters.